Green asset pricing - Ghassane Benmir; Ivan Jaccard; Gauthier Vermandel (European Central Bank (ECB), 2020)
Climate change is one of the biggest economic challenges of our time. Given the scale of the problem, the question of whether a carbon tax should be introduced is hotly debated in policy circles. This paper studies the optimal design of a carbon tax when environmental factors, such as air carbon dioxide emissions (CO2), directly affect agents' marginal utility of consumption. Our first result is that the optimal tax is determined by the shadow price of CO2 emissions. We then use asset pricing theory to estimate this implicit price in the data and find that the optimal tax is pro-cyclical. It is therefore optimal to use the carbon tax to "cool down" the economy during periods of booms and to stimulate it in recessions. The optimal policy not only generates large welfare gains, it also reduces risk premiums and raises the average risk-free real rate. The effect of the tax on asset prices and welfare critically depends on the emission abatement technology.
Keywords: Q58; G12; E32; 330; Climate Change; Compensation Effect; Bond Premium Puzzle; Natural Rate of Interest; Optimal Policy; Welfare